Traditional uses of medicinal plants practiced by the indigenous communities at Mohmand Agency, FATA, Pakistan - Muhammad Abdul Aziz; Muhammad Adnan; Amir Hasan Khan; Abdelaaty Abdelaziz Shahat; Mansour S. Al-Said; Riaz Ullah (BMC, 2018)
Abstract Background Plant-derived products have an imperative biological role against certain pathogenic organisms and were considered to be a major source of modern drugs. Rural people residing in developing countries are relying on traditional herbal medical system due to their strong believe and minimum access to allopathic medicines. Hence, ethnomedicinal knowledge is useful for the maintenance of community's based approaches under this medical system. Present study was carried out in an unexplored remote tribal area of Pakistan to investigate and document the existing ethnomedicinal knowledge on local flora. Methods Data was collected through semi-structured questionnaires from the community members and local herbalists. Use reports (URs) were counted for each species and analyzed through Linear Regression between the number of URs per family and number of plant species per family. Results A total of 64 medicinal plant species were recorded belonging to 60 genera and 41 families. Most frequently used plant families in ethnomedicines were Lamiaceae (8 species) and Asteraceae (7 species). Highest URs were recorded for Caralluma tuberculata N.E. Br. (49 URs) being followed by Thymus serphyllum L. (49 URs), Fagonia cretica L. (47 URs), Plantago lanceolata L. (45 URs), Periploca aphylla Decne. (44 URs), Citrullus colocynthis (L.) Schrad. (44 URs), and Sideroxylon mascatense (A.DC.) T.D.Penn. (44 URs). New ethnomedicinal uses were reported for Boerhaavia elongata Brandegee and Fumaria officinalis L. with confidential level of URs from the study area. Nineteen groups of health conditions were recorded during the course of study being treated with medicinal plants. Maximum number of 30 plant species was used to treat digestive problems. Most widely practiced mode of drugs' preparation and administration was powder. Leaves (30% plants) were the most frequently used plant parts in the preparation of ethnomedicinal recipes. Conclusions Current study is an important addition to the field of ethnomedicines. The study reports important medicinal plants from an area, which has not been investigated previously. Traditional knowledge is restricted to health practitioners and elder community members. This knowledge is at the verge of extinction because younger generation is not taking interest in its learning and preservation process. Hence, there is a dire need to phytochemically and pharmacologically test the investigated taxa for the validation of traditional knowledge.